Estudo numérico do acoplador duplo simétrico não linear de fibras de cristais fotônicos sob modulação PPM - Sousa, Carlos Maurício de (2013)
In this work, we present a numerical analysis for obtaining all-optical logic gates based on a Directional Coupler Nonlinear Symmetric Double (NLDC) in photonic crystal fibers (PCF) without loss, working with ultrashort pulses of 100 fs (femtoseconds) , to obtain gates AND / OR under Pulse Position Modulation (PPM). Research is conducted through numerical simulations, using the Runge-Kutta fourth order. Considering the operation of logic gates were used the four possible combinations to the inputs of two pulses fibers 1 and 2, the temporal position modulated (PPM) in the logic levels 0 or 1. Were investigated initially, the effects of a change in tuning parameter PMM (ε) in the displacement of the output pulse in each fiber, then we investigated the effects of the phase difference (ΔФ) between pulses of fundamental solitons input, suitably modulated, at offset output pulse in each fiber. In both applications, were considered anomalous dispersion of group velocity (GVD), second order dispersion (β2), the third-order dispersion (β3) and nonlinear effects SPM, SS and IRS. The results indicate that it is possible to achievement OR logic gate using phase control to an input pulse.